Pengukuran Jarak Lubang Pada Benda Padat Menggunakan Sensor Ultrasonik - Ivan Dwicahyo Pratomo; Abdul Rouf; Tri Wahyu Supardi (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2016)
The process of making solid object in general, not print with good so that holes can’t be seen directly visually. NDT (Non Destructive Testing) is a method for detecting holes and the quality of solid objects without damaging solid object one uses ultrasonic to detect holes a solid object which there are on internal solid object. This research aims to design an instrument for measuring distances holes of solid body using ultrasonic sensor and oscilloscope.The method used for the testing is the echo pulse which produce output of the wave amplitude shown oscilloscope. Function generator as input pulses 40 KHz to circuit amplifier then the transformator strengthened and continued to ultrasonic transmitter. Transmitter generated pulse to object and the pulse has reflection because it has holes an internal object. The reflection pulse is received by the receiver ultrasonic sensor and amplified by signal amplifier circuit, then the wave displayed on oscilloscope. The research showed that the smaller distance holes testing the wave amplitude obtained becomes larger and when the distance holes a solid object is longer the attenuation coefficient value the greater worth. The value of measurement error in using a tool value made author of 5 %.